2002
DOI: 10.1002/pi.898
|View full text |Cite
|
Sign up to set email alerts
|

Structured degradable poly(ether) hydrogels based on linear bifunctional macromonomers

Abstract: Hydrogels based on poly(ethylene oxide) (PEO) are suitable materials for numerous biomedical applications. Among the different ways to design such hydrogels, homopolymerization of bifunctional PEO macromonomers represents a promising approach. The present work discusses the extension of this crosslinking procedure to prepare degradable hydrogels. Poly(1,3‐dioxolane) (PDXL) hydrogels were synthesized directly in water (or in organic solvents) by free‐radical homopolymerization of α,ω‐methacryloyloxy PDXL macrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 16 publications
2
25
0
Order By: Relevance
“…The hydroxyl functions were transformed into alcoholates by addition, at room temperature, of a stoichiometric amount of diphenylmethyl potassium (the stoichiometry being determined by colorimetry), which provoked the viscosity of the reaction medium to increase, due to the formation of associations between chain ends. In the following step, methacryloyl chloride diluted in cyclohexane (1:10, v/v) was added to the living polymer solution, according to the procedure described elsewhere [12] (Scheme 2).…”
Section: Macromonomer Synthesis and Characterizationmentioning
confidence: 99%
“…The hydroxyl functions were transformed into alcoholates by addition, at room temperature, of a stoichiometric amount of diphenylmethyl potassium (the stoichiometry being determined by colorimetry), which provoked the viscosity of the reaction medium to increase, due to the formation of associations between chain ends. In the following step, methacryloyl chloride diluted in cyclohexane (1:10, v/v) was added to the living polymer solution, according to the procedure described elsewhere [12] (Scheme 2).…”
Section: Macromonomer Synthesis and Characterizationmentioning
confidence: 99%
“…PDXLs [21][22][23][24] were dissolved in dichloromethane and then treated with methacrylic acid in the presence of dicyclohexylcarbodiimide (DCCI) with 4-dimethylaminopyridine as catalyst. The resulting macromonomers were characterized by SEC for molar mass determination on a Waters Associates apparatus with a Waters 401 refractive index detector.…”
Section: Synthesis Of Poly(13-dioxolane) Macromonomersmentioning
confidence: 99%
“…In previous publications [3,10,21] we have shown that free radical homopolymerization of bifunctional PEO or PDXL macromonomers, when conducted in water at 60 8C, yields hydrogels in less than one hour. This result is attributed to the fact that, in an aqueous medium, PEO or PDXL macromonomers (which contain a hydrophilic chain but hydrophobic polymerizable methyl methacrylate end groups) are kept together by the aggregation of their ends (micellization).…”
Section: Synthesis and Properties Of Swollen Pdxl-conetworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, PDXL with functional groups is more interesting because it is used in the preparation of hydrogels, [3][4][5][6] which are suitable materials for numerous biomedical applications. Among the different ways of preparing such hydrogels, the homopolymerization of hydrophilic, bifunctional macromonomers, such as bifunctional poly(ethylene oxide), [7,8] methacryloyloxy-PDXL, [6,9] and acryloyloxy-PDXL, [10][11][12] represents a good approach.…”
Section: Introductionmentioning
confidence: 99%